Subluxation of scleral-fixated PC IOL caused by polypropylene suture degradation – case report - Kanigowska, Krystyna; Grałek, Mirosława; Czarnowska, Elżbieta; Zajączkowska, Agnieszka (Klinika Oczna / Acta Ophthalmologica Polonica, 2009)
The purpose of the study is to evaluate factors related to late-onset of lens subluxation in transscleral sutured posterior chamber IOL. We report a child, which required surgical treatment for dislocation of a scleral-sutured PC IOL. 11 years earlier the secondary lens implantation with scleral fixation was performed in 4 years old boy. The first surgical procedure included an anterior victrectomy and suturing a single- piece PMMA IOL under the scleral flaps with a 10-0 polipropylene suture. The second – included explantation of the dislocated lens. Optic and scanning electron microscopy was used to analyze the surface of the explanted remnants of the breakage suture. Microscopic findings indicate that the late suture breakage and subluxation of suture-fixated PC IOL was due to the degradation of polypropylene suture.